Carbon dioxide pneumoperitoneum may alter ovarian apoptosis: An experimental study - Suleyman Guven; Hidayet Sal; Emine Seda Guvendag Guven (Wolters Kluwer Medknow Publications, 2021)
Objective: The aim of this study was to evaluate ovarian immunohistochemical CD95 expression in a rabbit carbon dioxide pneumoperitoneum model. Materials and Methods: The study group including seven rabbits was subjected to intra-abdominal pressure (IAP) (12 mmHg); the control group was not subjected to IAP (the sham group, n = 7). At the end of the experiment, ovariectomy was performed. Immunohistochemical stained histologic specimen of the ovary with CD95 was evaluated. Based on the degree of cytoplasmic or membranous staining for CD95 from 0 (none) to 3 (severe), a microscopic apoptosis scoring system was used. Results: Statistically significantly higher apoptosis scores in ovarian surface epithelial cells (2.57 ± 0.53, vs. 1.14 ± 0.38, P = 0.002, Mann-Whitney U-test, respectively), follicular epithelial cells (2.85 ± 0.38, vs. 1.85 ± 0.38, P = 0.002, Mann-Whitney U-test, respectively), and stromal cells (2.71 ± 0.49, vs. 1.29 ± 0.49, P = 0.002, Mann-Whitney U-test, respectively) were observed in pneumoperitoneum group, compared with no-pneumoperitoneum group. Conclusion: Even at safe IAP (12 mmHg) for an acceptable operation time period, there was a significant increase in apoptosis of ovarian cells.